COVID-19 severe acute respiratory syndrome in Brazilian newborns in 2020-2021 - Andressa Rocha Pereira; Maria dos Remédios Freitas Carvalho Branco; Silmery da Silva Brito Costa; Denise Ailine Monteiro Lopes; Vanessa Vieira Pinheiro; Daniel Cavalcante de Oliveira; Amanda Namíbia Pereira Pasklan; Jamesson Amaral Gomes; Alcione Miranda dos Santos; Mônica Elinor Alves Gama (Revista Brasileira de Epidemiologia, 2023)
ABSTRACT Objective: To describe the clinical characteristics of cases of COVID-19 severe acute respiratory syndrome (SARS) in Brazilian newborns (NBs) in 2020 and 2021, recorded in the Influenza Epidemiological Surveillance Information System (Sistema de Informação da Vigilância Epidemiológica da Gripe — SIVEP-Gripe). Methods: The variables analyzed were gender, race/skin color, hospitalization, intensive care unit (ICU) admission, use of ventilatory support, signs and symptoms (fever, cough, O2 saturation<95%, dyspnea, respiratory distress, diarrhea, and vomiting), progress (death or cure), risk factors/comorbidities. Categorical variables were expressed as absolute and relative frequencies. Results: We found 1,649 records of COVID-19 SARS in NBs, with a predominance of multiracial babies in both years. The most frequent symptoms in 2020 and 2021 were, respectively: respiratory distress (67.0 and 69.7%), fever (46.3 and 46.2%), and cough (37.0 and 46.3%). In 2020, 30.5% of patients received invasive ventilatory support; in 2021, this number was 41.6%. In addition, more than 55% of cases required ICU admission, and over 16% died. Conclusion: We emphasize the high proportion of cases that required intensive care and progressed to death.